Complete national parks of the United States : 400+ parks, monuments, battlefields, historic sites, scenic trails, recreation areas, and seashores - White, Mel, 1950- (National Geographic, 2022)
"This reference is the ultimate travel planner for all things national parks, scenic trails, seashores, historic areas, and more"--